2003
DOI: 10.1080/01448765.2003.9755279
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Agronomic Effects of Burning and Biomass Removal in a Typical Slash and Burn Rotation System in Southern Cameroon

Abstract: Little research on slash and burn systems has investigated whether effects of burning are due to the fire per se or to the removal of biomass from the soil surface. In this experiment, the aim was to assess the effects of burning versus no burning and mulching versus no mulching on maize yields, chlorophyll levels, nutrient uptake and soil properties in a short fallow 'no external input' system in two consecutive cropping seasons on an ultisol in southern Cameroon. In the second maize cropping season, treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(14 reference statements)
0
9
1
Order By: Relevance
“…reported similar effects and related them largely to problems of plant establishment when slash was retained. Contrary to that, Norgrove et al (2003) reported from the same area negative effects of burning on maize yields. Koutika et al (2001) could not discern effects on particulate organic matter of annual burning in a 4 year-old maize-cover crop relay system.…”
Section: Discussioncontrasting
confidence: 60%
“…reported similar effects and related them largely to problems of plant establishment when slash was retained. Contrary to that, Norgrove et al (2003) reported from the same area negative effects of burning on maize yields. Koutika et al (2001) could not discern effects on particulate organic matter of annual burning in a 4 year-old maize-cover crop relay system.…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand, the export of the wood would result in a less intensive burn with potentially less negative effects on the soil. Norgrove et al (2003) have shown at the same site that burning of short fallow biomass has a negative impact on crop growth. No information on the consequences of nutrient removal with wood in short fallow systems could be found.…”
Section: Discussionmentioning
confidence: 95%
“…Maize dry grain yields were estimated through plot harvests, grain separation, and dry matter determination (Norgrove et al 2003a; Hauser et al 2008). Plants were counted, cobs were removed, counted, husked, and weighed fresh.…”
Section: Methodsmentioning
confidence: 99%
“…Due to theft and a requirement to abandon the latter field, a field of plantain after 20 years of fallow was additionally included (Hauser and Mekoa 2009 ; Hauser et al 2012a ). Additionally, we selected plots with reduced fallow scenarios whereby maize was cropped after 2 years of fallow (Norgrove et al 2003a , 2003b ); and plantain after 6 years of fallow (Norgrove et al 2003a , 2003b ). Site locations were Andok, Ekombitié, Ngoumbou, Bilik, and Zoatoupsie, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation